AMPK : methods and protocols - Andris, Fabienne; Balligand, Jean Luc; Beauloye, Christophe; Bertrand, Luc; Birk, Jesper B.; Neumann, Dietbert 1968-; Viollet, Benoît 1968- (New York, N.Y. : Humana Press, 2018)
This volume explores the latest methods used to study AMPK by computational, biochemical, biophysical, cellular, and ex vivo and in vivo approaches. The chapters in this book cover specific topics, such as methods to measure change in cellular energy metabolism and analyze metabolic pathways regulated by AMPK; bioinformatics tools to identify AMPK targets; knockdown of AMPK by CRISPR-Cas9; production and crystallization of full-length human AMP-activated protein kinase; cell-free assays to measure the effects of regulatory ligands on AMPK; use of sensors of AMPK activity; AMPK protein interaction by yeast two-hybrid; the role of AMPK in inflammation and autophagy; analyzing the AMPK function in C. elegans and mammals (with special focus on skeletal muscle, blood vessels, kidneys, pancreatic islets and hypothalamus); and human γ2 AMPK mutations. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.
Keywords: PROTEINA QUINASAS -- MANUALES DE LABORATORIO